Impact of CCND1 amplification on the prognosis of hormone receptor–positive, HER2-negative breast cancer patients—correlation of clinical and pathological markers - Hanf, Dorothea; Fasching, Peter; Gaß, Paul; Beckmann, Matthias; Hack, Carolin; Heindl, Felix; Häberle, Lothar; John, Nelson; Erber, Ramona; Press, Michael F.; Rübner, Matthias; Pöschke, Patrik (Breast Cancer Research and Treatment, 2024)
Purpose: The cyclin D1 gene (CCND1) encodes a key cell-cycle regulatory protein. Resistance to endocrine therapy is reportedly observed more often in patients with CCND1-amplified tumors. CCND1 amplification is known to be a driving event in breast cancer, but contradictory findings are reported for its association with prognosis. This study therefore investigated the prognostic value of CCND1 amplification in hormone receptor (HR)-positive breast cancer patients. Methods: A cohort of 894 unselected breast cancer patients from the Bavarian Breast Cancer Cases and Controls (BBCC) study was included. The CCND1 amplification rate was evaluated in tissue microarrays using fluorescence in situ hybridization. A CCND1/CEP11 ratio ≥ 2.0 was considered amplified. Statistical analysis was conducted on cases with ratios based on a range of 20–100 nuclei analyzed per case. A univariable Cox regression model was fitted with disease-free survival (DFS) and overall survival (OS). Results: CCND1 gene status was assessable in 511 patients. The CCND1 amplification rate was 12.9% (66 patients). Most patients with CCND1 amplification had luminal B-Like—(51.5%, n = 34) or luminal A-Like tumors (25.8%, n = 17), 13 patients with HER2-positive disease (19.7%) and only two patients had triple-negative tumors (3.0%). Survival analysis, focused on HR-positive, HER2-negative patients, showed no statistically significant differences in the DFS and OS with and without CCND1 amplification (P = 0.20 and 0.14, respectively, in the unadjusted analysis). Conclusions: CCND1 amplification is a recurring event in breast cancer, occurring most frequently in luminal B-like and HER2-amplified subtypes. A trend toward less favorable outcomes was observed among CCND1-amplified HR-positive, HER2-negative tumors.
CRIS-Team Scopus Importer:2024-12-06
Keywords: Amplification; Breast cancer; CCND1; FISH; Prognosis